2013
DOI: 10.1002/gea.21435
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Phreatic Palaeogroundwater Levels in a Geoarchaeological Context: A Case Study in Flanders, Belgium

Abstract: The complex debate on prehistoric settlement decisions is no longer tackled from a purely archaeological perspective but from a more landscape‐oriented manner combined with archaeological evidence. Therefore, reconstruction of several components of the former landscape is needed. Here, we focus on the reconstruction of the groundwater table based on modeling. The depth of the phreatic aquifer influences, for example, soil formation processes and vegetation type. Furthermore, it directly influences settlement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To deal with extremely long time scales, models should be able to incorporate long‐term changes in climate, landforms, and other relevant boundary conditions. Integrated methodological approaches need to be developed to verify such models beyond the time‐scale of instrumental observations, for example, by including proxy variables serving as (paleo)indicators of past hydrological conditions (e.g., vegetation, soil, or historical archives; Zwertvaegher et al, 2013; Zlinszky and Timár, 2013). As in simulating soil formation, many input variables are uncertain since they are in essence unknown for future conditions.…”
Section: Soil Modeling and Ecosystem Servicesmentioning
confidence: 99%
“…To deal with extremely long time scales, models should be able to incorporate long‐term changes in climate, landforms, and other relevant boundary conditions. Integrated methodological approaches need to be developed to verify such models beyond the time‐scale of instrumental observations, for example, by including proxy variables serving as (paleo)indicators of past hydrological conditions (e.g., vegetation, soil, or historical archives; Zwertvaegher et al, 2013; Zlinszky and Timár, 2013). As in simulating soil formation, many input variables are uncertain since they are in essence unknown for future conditions.…”
Section: Soil Modeling and Ecosystem Servicesmentioning
confidence: 99%
“…The most striking feature is the substantial and rather certain thickness of Holocene sediments in the western part of the Moervaart depression and the eastern parts of the floodbasins of Sleidinge (Figure 1, Figure 6: area 2). In the same study area, Zwertvaegher et al (2013a) concluded, based on simulation of the palaeohydrology, that the early Holocene was characterized by a rapid increase of groundwater levels and a decrease in spatial wetness gradients, leading to a less attractive landscape for hunter-gatherers. In the same study area, Zwertvaegher et al (2013a) concluded, based on simulation of the palaeohydrology, that the early Holocene was characterized by a rapid increase of groundwater levels and a decrease in spatial wetness gradients, leading to a less attractive landscape for hunter-gatherers.…”
Section: Mapped Thickness Of Holocene Sedimentsmentioning
confidence: 99%
“…In stable landscapes with shallow water tables, a 3D-groundwater model can be applied to generate the lower boundary condition (e.g., a time series of the annual average water table depth) for the 1-D profile model (Zwertvaegher et al, 2013a). After running the 1D-model, the results are again interpolated (Zwertvaegher et al, 2013b).…”
Section: Soilscape Genesis By Distributed Profile Modelingmentioning
confidence: 99%